2013
DOI: 10.1073/pnas.1306373110
|View full text |Cite
|
Sign up to set email alerts
|

Host-induced gene silencing of cytochrome P450 lanosterol C14α-demethylase–encoding genes confers strong resistance to Fusarium species

Abstract: Head blight, which is caused by mycotoxin-producing fungi of the genus Fusarium, is an economically important crop disease. We assessed the potential of host-induced gene silencing targeting the fungal cytochrome P450 lanosterol C-14α-demethylase (CYP51) genes, which are essential for ergosterol biosynthesis, to restrict fungal infection. In axenic cultures of Fusarium graminearum, in vitro feeding of CYP3RNA, a 791-nt double-stranded (ds)RNA complementary to CYP51A, CYP51B, and CYP51C, resulted in growth inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
332
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(366 citation statements)
references
References 46 publications
10
332
1
5
Order By: Relevance
“…A wide range of transgenic crops expressing dsRNAs that are subsequently processed into sRNAs targeting essential and/or pathogenicity genes are more resistant to viruses, viroids, bacteria, fungi, oomycetes, nematodes, and insects (Cai et al 2018). Several studies demonstrated that cereals can be protected from Fusarium species by expressing dsRNAs targeting essential fungal genes such as Chitin synthases, β-1,3-Glucan synthase, or the azole fungicide target Cytochrome P450 lanosterol C-14 α-demethylase (Koch et al 2013;Cheng et al 2015;Chen et al 2016). Moreover, banana could be protected from Fusarium wilt caused by the soilborne fungus Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of transgenic crops expressing dsRNAs that are subsequently processed into sRNAs targeting essential and/or pathogenicity genes are more resistant to viruses, viroids, bacteria, fungi, oomycetes, nematodes, and insects (Cai et al 2018). Several studies demonstrated that cereals can be protected from Fusarium species by expressing dsRNAs targeting essential fungal genes such as Chitin synthases, β-1,3-Glucan synthase, or the azole fungicide target Cytochrome P450 lanosterol C-14 α-demethylase (Koch et al 2013;Cheng et al 2015;Chen et al 2016). Moreover, banana could be protected from Fusarium wilt caused by the soilborne fungus Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing F. graminearum CYP51 genes in vitro , through the exogenous application of a 791‐nucleotide dsRNA complementary to each of the three CYP51 paralogs, inhibited fungal growth and caused the abnormal branching of developing hyphae. Moreover, detached leaves of both transgenic Arabidopsis and barley plants expressing the same dsRNA were more resistant to F. graminearum infection compared with wild‐type plants,36 demonstrating the capacity of HIGS to silence fungal genes and impede infection.…”
Section: Higs and Fusarium Head Blightmentioning
confidence: 98%
“…The majority of studies carried out with transgenic Bt maize demonstrated that these plants were also less contaminated with Fusarium mycotoxins, including fumonisin, DON and zearelone than non‐Bt maize 35. A more recent strategy includes direct RNAi approaches, such as HIGS and SIGS, that have successfully silenced essential fungal genes and/or essential biosynthetic pathways 33, 34, 36, 37. Although CYP51 is found in most eukaryotic organisms, the average nucleotide identity between CYP51 genes from different species is very low (25–30%).…”
Section: Higs and Fusarium Head Blightmentioning
confidence: 99%
See 2 more Smart Citations